Electronic structure of Tl 2 CdSnSe 4 compound studied by XPS Method - Ткач, В. А.; Хижун, О. Ю. (НТУ ДП, 2023)
Quaternary chalcogenide semiconductors with general chemical composition I 2 –II–IV– Q 4 (I – Cu, Ag; II–Zn, Cd, Hg; IV–Si, Ge, Sn; Q–S, Se, Te) became a point of great interest of many material scientists due to their great combination of physical and chemical properties. Band gap width, p-type conductivity, thermoelectrical and optical properties make these compounds as promising materials for solar energy conversion applications or nonlinear optic devices.